I want to break free: Successor Emancipation in Family Business - Miruna RADU-LEFEBVRE; Vincent Lefebvre (Boletín de Estudios Económicos)
Family business successors live at the nexus of past, present and future, nourished and inspired by past legacies while also craving to build a brand-new future. The senior generation is generally the guardian of firm continuity in charge of preserving past achievements, whereas the next generation might dream about introducing change and innovation within the current landscape of the family firm. Yet these attempts too often trigger resistance and anxiety in the senior generation, who might respond with increasing control and suspicion to any tentative of challenging the status quo such as transforming current products, services, business models, or organizational structures. Successors operate at the intersection of these opposite forces of conservatism and reform, and one of their major issues is that they need to handle them effectively, that is without jeopardizing family relations and harmony nor losing themselves into the process. Unless they succeed in doing so, succession failure might follow. By combining two different streams of literature grounded in distinct disciplines, namely succession literature in family business and emancipation literature in entrepreneurship, we reveal successor emancipation as a novel explanation of why successions fail and offer some practical advice on how to handle these tensions in intra-family succession.